PENDEKATAN SOSIOLOGI DAN ANTROPOLOGI DALAM STUDI ISLAM - Diah Ainun Khafidloh; Muhammad Hori; Nur Rofi’ah; Saiful Anwar; Siti Aminah (PT. Hasba Edukasi Mandiri, 2025)
Sociological and anthropological approaches in Islamic studies to understand religion contextually in modern society, where religion is often a source of problems due to a lack of understanding of social sciences. The sociological approach (ilm al-ijtimaiyah) studies the social aspects of Islam such as societal structure, group interactions (in-group/ out-group, primary/secondary, paguyuban /patembayan), as well as functionalist and symbolic interactionist perspectives to implement Islamic teachings universally and prevent misconceptions, The anthropological approach examines humans holistically—physical, cultural, and belief—through branches such as cultural, religious, and linguistic anthropology, with a focus on real religious practices in society, such as Clifford Geertz's work on santri-priyayi-abangan in Java. These two approaches complement each other to analyze the phenomenon of Islam across cultures, emphasizing holism, field observation, and the inseparable relationship between religion and culture (Nurcholish Madjid)